Impact of MA Temporary Storage Process on the Reduction of Final Disposal Burden in the Advanced Nuclear Fuel Cycle - Okamura Tomohiro; Nasase Masahiko; Takeshita Kenji; Shimada Takashi; Konishi Yuki; Nishimura Keisuke; Ishida Hitomi; Yamamura Tomoo (EPJ Web of Conferences)
Separating minor actinides (MA) from high-level radioactive waste (HLW) is an effective option for reducing the burden of final disposal. However, the recovered MA must be transmuted in fast reactors (FR) or similar technologies. The widespread deployment of FR is expected in the latter half of the 21st century. In this study, we evaluated the introduction of a temporary MA storage process to bridge the time gap between the early introduction of MA separation and the deployment of FR with adequate transmutation capacity. The results showed that the MA temporary storage process effectively mitigates the burden of final disposal and MA temporary storage allows the amount of recovered MA to be managed independently of the FR capacity.